MARINE RADIOCARBON RESERVOIR AGE ALONG THE CHILEAN CONTINENTAL MARGIN - Merino-Campos, Victor; De Pol Holz, Ricardo Hernán; Southon, John; Latorre, Claudio; Collado-Fabbri, Silvana (My University, 2019)
We present 37 new radiocarbon (C-14) measurements from mollusk shells fragments sampled along the Chilean continental margin and stored in museum collections with known calendar age. These measurements were used to estimate the modern pre-bomb regional marine C-14 age deviations from the global ocean reservoir (Delta R). Together with previously published data, we calculated regional mean Delta R values for five oceanographic macro regions along the coast plus one for a mid-latitude open ocean setting. In general, upwelling regions north of 42 degrees S show consistent although sometimes highly variable Delta R values with regional averages ranging from 141 to 196 C-14 yr, whereas the mid-latitude open ocean location of the Juan Fernandez archipelago and the southern Patagonian region show minor. Delta R of 40 +/- 38 C-14 yr, and 52 +/- 47 C-14 yr respectively. We attribute the alongshore decreasing pattern toward higher latitudes to the main oceanographic features along the Chilean coast such as perennial coastal upwelling in northern zone, seasonally variable upwelling at the central part and the large freshwater influence upon the southern Patagonian channels.
Keywords: chile; radiocarbon ams dating; reservoir correction; reservoir effect; upwelling